Pediatricians' awareness of galenic drugs for children with special needs: a regional survey - Francesca Burlo; Davide Zanon; Paola Minghetti; Valentina Taucar; Giulia Benericetti; Giada Bennati; Egidio Barbi; Lucia De Zen (BMC, 2023)
Abstract The prevalence of children with medical complexity is increasing, therefore drug formulations must be updated in accordance with their needs. Furthermore, a different drug formulation may be also needed for patients who require a very low dosage which is not easily reachable with those of the industrial products or for those following a ketogenic diet. Galenic (or compounded) drugs have been recently pointed out as effective in treating children. Nonetheless, their knowledge among healthcare providers is limited. We investigated how much did pediatricians know about galenic compounds by a short questionnaire administered to family and hospital pediatricians and pediatric residents in Friuli Venezia Giulia, Italy. We collected answers from 65 family pediatricians (57,5%), 39 hospital pediatricians (36,1%), and 47 pediatric residents (41,2%). Overall, both family and hospital pediatricians substantially know what is a galenic compound and the indications to its use. Of note, most of pediatricians ignore which is the legislation that allows the galenic compounds' preparation and use, and which is the correct procedure to prescribe them. Moreover, half of the hospital pediatricians and one-third of the family ones erroneously stated that galenic formulations cost more or like the industrial products, and around the 15% of both categories affirmed that galenic compounds are less safe than the commercial product. In conclusion, the use of galenic drug may significantly improve children's and caregivers' quality of life. We believe that all pediatricians should be updated on this quite new and interesting topic.